Ambiguity and the centipede game: strategic uncertainty in multi-stage games - Eichberger, Jürgen; Grant, Simon; Kelsey, David (Discussion paper series, 2017)
We propose a solution concept for a class of extensive form games with ambiguity. Specifically we consider multi-stage games. Players have CEU preferences. The associated ambiguous beliefs are revised by Generalized Bayesian Updating. We assume individuals take account of possible changes in their preferences by using consistent planning. We show that if there is ambiguity in the centipede game it is possible to sustain 'cooperation' for many periods as part of a consistent-planning equilibrium under ambiguity. In a non-cooperative bargaining game we show that ambiguity may be a cause of delay in bargaining.
Aus: Discussion Paper Series / University of Heidelberg, Department of Economics ; 0638
Keywords: Arbeitspapier; Graue Literatur